Laboratory tests to characterize the mastic of bituminous mixtures - Silva, Hugo Manuel Ribeiro Dias da (2005)
The bituminous mixtures are composed by more than one material (i.e. coarse and fine aggregates, filler and bitumen). The components are simultaneously present and contribute to the response of the mixture. Some studies have pointed out the mastic influence in the bituminous mixtures behaviour. The mastic is a mix of bitumen, filler and fine aggregates (maximum dimension of 2 mm) and represents the binder of the coarse aggregates in the bituminous mixtures. This research intends to observe the mechanical behaviour of the mastic as part of the bituminous mixture and it correlation with the bituminous mixtures. The mechanical performance of the mastic was observed in laboratory using tensile, compression and shear tests. Bituminous mixtures with the mastics defined in this work were made and then characterized using the same tests and the results were correlated to the mastic behaviour. The main conclusions explain the influence of the mastic in the performance of a bituminous mixture.